Availability of rehabilitation services for communication disorders in Sri Lanka: a cross-sectional survey - Samanmali P Sumanasena; Nimisha Muttiah; Rajitha Wickremasinghe; A V Caldera; T U Munasinghe; K M N Perera; D Tilakarathne; M K R R Peiris; E Thamilchelvan; Chamilka Sooriyaarachchi; Mohamed Naseem Nasma; R M Manamperige; et al. (BMJ Open)
Objectives To describe the rehabilitation services available for communication disorders in Sri Lanka and to estimate the adequacy of the services in provinces and districts of the country.Setting The study considered government and private institutions, which provide rehabilitation services for communication disorders in Sri Lanka.Participants Institutions providing services of speech–language pathologists, audiologists and audiology technicians in Sri Lanka.Primary and secondary outcome measures We investigated the number of government hospitals and private institutions, which provide speech–language pathology and audiology services in Sri Lanka as the primary outcome measure. A number of speech–language pathologists, audiologists and audiology technicians working in the institutions were obtained from records and institution-based inquiries to identify the adequacy of the services in the country as the secondary outcome measure.Results Of the 647 government hospitals that provide free healthcare services in the country, 45 and 33 hospitals had speech and language therapy and audiology units, respectively. Government hospitals do not have audiologists but only have audiology technicians. The number of speech and language therapists and audiology technicians in the government sector per 100 000 population in the country was 0.44 and 0.18, respectively. There were wide variations in specialist to population ratio between districts. 77 private centres provide speech therapy services in 15 out of the 25 districts; 36 private centres provide audiological evaluations in 9 districts.Conclusions The number of specialist speech and language therapists and audiologists is not sufficient to provide adequate rehabilitation services for communications disorder for the Sri Lankan population. Not recruiting audiologists to the government sector affects the management of hearing impairment in the affected.